Redesain Gedung Rumah Sakit Ibu dan Anak Nirmala Kediri Berdasarkan Permenkes Nomor 40 Tahun 2022 - Fitri, Liena Nurul (Jurnal Vokasi Teknik Sipil, 2023)
Improving maternal and child health facilities and infrastructure is urgently needed, especially when the population is growing. Therefore, it is necessary to build quality healthy buildings in order to achieve optimal health status. The construction project for the RSIA Nirmala Kediri building is one of the construction projects for the Mother and Child Hospital in Kediri, where several areas and room zoning still have discrepancies, according to the Minister of Health. The purpose the study is: Evaluate the plan drawings of the House project Sick Mother and Child Nirmala and adjust with the standardization of PERMENKES No. 40 of 2022 .This project research type is Quantitative using Primary Data and Secondary Data. The results of the calculation of the recapitulation of the area of space that is not suitable are 6 rooms. With 5 rooms that are not following Permenkes standards, and 1 room that does not yet exist. To obtain a percentage of 6/39x100% = 15.38% and the appropriate spaces is 33 spaces, the percentage is obtained: 33/39x100% = 84.62%. The results of the redesign regarding the Nirmala Kediri mother and child hospital building resulted in several rooms being redesigned in following Permenkes No. 40 of 2022. The addition of the area of the ER, R.operations, NICU, R.jenazah rooms and the addition of R.PK. Zoning shifts were also made for inpatient VIP class building A, class I inpatient care building A, class III inpatient care building C. Most of the rooms of the Nirmala Kediri Mother and Child Hospital building were still maintained because they were in accordance with the provisions of the Minister of Health. However, for several rooms that did not comply with Permenkes No. 40 of 2022, a redesign was carried out. It is hoped that the planners for the construction of the Nirmala Mother and Child Hospital building in Kediri will refer more to the regulations that have been made.